Skipjack Tuna Availability for Purse Seine Fisheries Is Driven by Suitable Feeding Habitat Dynamics in the Atlantic and Indian Oceans - Druon, Jean-Noël; Chassot, Emmanuel; Murua, Hilario; Lopez, Jon (Frontiers in Marine Science, 2017)
An Ecological Niche model was developed for skipjack tuna (Katsuwonus pelamis, SKJ) in the Eastern Central Atlantic Ocean (AO) and Western Indian Ocean (IO) using an extensive set of presence data collected by the European purse seine fleet (1998 – 2014). Chlorophyll-a fronts were used as proxy for food availability while mixed layer depth, sea surface temperature, dissolved oxygen, salinity, current intensity and height anomaly variables were selected to describe SKJ’s abiotic environmental preferences. The resultant ecological niche included both mesoscale eddy-type productive features that displayed latitudinal range in the IO to large scale upwelling systems that shrink and swell seasonally in the AO. Overall, 83% of all free swimming school sets (FSC) and 75% of drifting fish aggregating device sets (dFAD) that contained SKJ occurred within 25 km of favorable feeding habitat. In the AO, 34% of dFAD sets were made more than 100 km away from this habitat, mostly in the surface chlorophyll-a poor environment of the Guinea Current. These distant sets represent 10% of dFAD sets in the IO and 8% of all FSC sets. Our results suggest that the Mozambique Channel in the IO, with its simultaneously favorable feeding and spawning conditions, may seasonally offer a better SKJ nursery habitat than the Guinea Current which shows a substantially poorer feeding capacity. With the exception of this latter area, our results also suggest that fishing accessibility will be higher in months where the size of the favorable feeding habitats are reduced, likely because this reduction drives a geographical contraction in SKJ populations. The observed relationship between the annual size of favorable feeding habitat and both annual catch rates and total catches in the IO is consistent with the near-full exploitation of this stock that has occurred since the 2000s. Moreover, it suggests that annual habitat size could be used as an indicator of growth capacity for this highly productive stock. Habitat monitoring, as part of a dynamic fisheries management approach, should contribute to the sustainable exploitation of SKJ by providing information on the climate-dependent aspects of stock variability and the effects of dFAD deployment in food-rich habitats.